Rapid and Sensitive Liquid Chromatographic Method for Determination of Paclitaxel from Parenteral Formulation and Nanoparticles - Kollipara, S. (Medknow Publications, 2010)
A simple and fast reversed phase liquid chromatographic method was developed for estimation of paclitaxel in commercially available parenteral formulation and nanoparticles. Separations were carried out using mobile phase consisting of acetonitrile and 20 mM potassium dihydrogen phosphate (45:55, v/v) on Lichrocart(®) C(18) analytical column at a flow rate of 1 ml/min and detection wavelength of 230 nm. The developed method exhibited linearity over an analytical range of 50-2000 ng/ml with regression equation, mean peak area= 137.58 concentration (ng/ml)+1765.94, (R(2) =0.9999). The method demonstrated selectivity with no interfering peaks eluting near the vicinity of drug peak. The method was found to be sensitive with detection and quantification limits of 7.57 ng/ml and 22.94 ng/ml. The method has shown consistent and good recoveries from parenteral formulation (100.06±0.86%) and nanoparticles (100.43±0.91%). The method was successfully employed for the analysis of in vitro release study samples of nanoparticle formulation. The method was also applied for determination of paclitaxel content in various pharmaceutical formulations.